Fish meal as a protein source for holstein steer calves - Morrill, J.L.; Laster, J.F.; Morrill, J.M.; Feyerherm, A.M. (Kansas Agricultural Experiment Station, 2011)
Holstein steer calves (n = 96) were on experiment from 8 to 18 wk of age. Control calves were fed a diet in which all supplemental protein was from soybean meal; in the experimental diet, part of the soybean meal was replaced by fish meal. Both feeds were readily consumed, and consumption did not differ between treatments. Gains of calves fed fish meal were greater (P = .10) during the first 8 wk of the experiment; however, over the entire experiment, the difference was not significant. Overall results suggest that fish meal may improve weight gains and feed efficiency of younger and smaller calves.
Keywords: Calves; Grower diets; Fish meal; Protein source